Tea Nutraceuticals: Unveiling Health Benefits and Bioactive Components a Review - Sravya, Gopi; Chavan, Dr. Sagar M; Ghatge, Dr. Jayant; A, Rasika; Prathapan, Dr. K. (International Journal of Environment, Agriculture and Biotechnology, 2024)
Nutraceuticals are medicinal foods that plays an important role in maintaining well-being, enhancing health, modulating immunity and thus preventing and treating specific diseases. Nutraceuticals can be defined as substances that have physiological benefits or protection against chronic diseases. Nutrients can be used to improve health, slow the aging process, prevent chronic disease, increase life expectancy, and support body structure and function. Camellia sinensis plant provides different types of tea including black, green, oolong, yellow, brick and white tea. Tea is one of the main beverages consumed around the world, but it is only successfully enjoyed with water for fitness and enjoyment. This review article discusses the analysis of tea nutrients and important bioactive compounds. It also describes the important health benefits of tea consumption. Important bioactive compounds in tea include antioxidants that have been shown to manage diabetes and prevent heart health and digestive diseases and polyphenols are known to reduce inflammation and the growth of cancer cells. In addition to the many known facts, future research will include further investigation into the molecular interactions and other therapeutic benefits of its bioactive compounds, so that everyone can better understand its importance.